Dampak Perubahan Kurikulum Terhadap Daya Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam Di Madrasah Aliyah - Abdurrahman, Yahya; Mubarok, Dede Husni (EDUPEDIA Publisher, 2025)
The curriculum changes in education in Indonesia, including the Islamic Education (PAI) subject at the Madrasah Aliyah level, aim to improve the quality of education in line with the development of the times. New curricula, such as the 2013 Curriculum and the Merdeka Curriculum, bring various changes in teaching and learning approaches. This article aims to analyze the impact of curriculum changes on students' learning capacity in the PAI subject at Madrasah Aliyah. This research uses a qualitative approach with a literature review discussing the various impacts of curriculum changes on the understanding and application of PAI material among students. The research results show that curriculum changes have a positive effect on students' motivation, understanding, and character but also face several challenges in implementation. Therefore, a collaborative effort between teachers, students, and the madrasah is necessary to maximize the positive impact of these curriculum changes.